Ufuque Lucknowi: Religious Neo- Revivalism and his Translations of the Religious Texts - Dr. Asif Zahri; Tafseer Hussain (Zaban-o-Adab, 2021)
This paper aims to discuss the translation of religious texts by Munshi Dwarka Prasad Ufuq. Born in Lucknow in the colonial period. He had command over Sanskrit, Hindi, and English along with Urdu. He has translated many religious texts from Sanskrit, including Tulsi Das’s Ramayana and Ramayan Valmiki. In his poetry he is found himself in a dilemma as on one hand he dreams revival of the Sanatan Dharma and on the other he wishes to strengthen Hindu-Muslim unity.